2015
DOI: 10.1186/s13071-015-0852-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmission efficiency of the plague pathogen (Y. pestis) by the flea, Xenopsylla skrjabini, to mice and great gerbils

Abstract: BackgroundPlague, a zoonotic disease caused by Yersinia pestis, is characterized by its ability to persist in the plague natural foci. Junggar Basin plague focus was recently identified in China, with Rhombomys opimus (great gerbils) and Xenopsylla skrjabini as the main reservoir and vector for plague. No transmission efficiency data of X. skrjabini for Y. pestis is available till now.MethodsIn this study, we estimated the median infectious dose (ID50) and the blockage rates of X. skrjabini with Y. pestis, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…In this respect, the extended phenotype triggered by the full blockage of the foregut of the fleas is one of frenzied feeding and regurgitation of the bacteria, and is estimated to increase the probability of transmission of the disease to 25-50% per flea per bite, compared with the low 0-10% probability of early-phase transmission per flea during the 3-day time window of earlyphase transmission 29 . The probability of plague transmission is ultimately dependent on multiple factors, such as flea species, temperature, and blood source 7,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the extended phenotype triggered by the full blockage of the foregut of the fleas is one of frenzied feeding and regurgitation of the bacteria, and is estimated to increase the probability of transmission of the disease to 25-50% per flea per bite, compared with the low 0-10% probability of early-phase transmission per flea during the 3-day time window of earlyphase transmission 29 . The probability of plague transmission is ultimately dependent on multiple factors, such as flea species, temperature, and blood source 7,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…pestis in the feces before the bacteria can multiply and form the large biofilm aggregates that typify a chronic infection. Frequent blood meal acquisition and defecation are also characteristic of Xenopsylla skrjabini , a flea that will normally feed several times a day on great gerbils [ 47 ]. Infected X .…”
Section: Discussionmentioning
confidence: 99%
“…10 The results indicated that a new plague focus, with an area of 16,000 km 2 , had emerged in Junggar Basin, in which the great gerbil was the main host 12 and X. skrjabini the main vector. 13 Understanding the phenotypic features and genetic diversity of Y. pestis isolates is important in characterizing a plague focus and contributes to the prevention and control of plague. Molecular genotyping and evolutionary analyses were used to describe the phylogenetic positions of the Junggar strains, including a multiple-locus variable number of tandem repeats analysis (MLVA), which is based on the diversity of variable numbers of tandem repeats (VNTR), 14,15 typing with clustered regularly interspaced short palindromic repeats (CRISPR), which is based on the varying compositions of the spacer arrays in three CRISPR loci in the genome, 16 and whole-genome single-nucleotide polymorphism (SNP) analysis.…”
Section: Introductionmentioning
confidence: 99%